An evaluation of differential reinforcement with stimulus fading as an intervention for medical compliance. Issue 3 (13th February 2020) - Stuesser, Hailee A.; Roscoe, Eileen M.
Abstract : Individuals with autism spectrum disorder (ASD) often exhibit noncompliance during medical exams. One intervention used to address this concern is differential reinforcement. Although differential reinforcement includes extinction, it may not be feasible or safe to implement extinction during medical exams. In the current study, we evaluated differential reinforcement without extinction and differential reinforcement without extinction plus stimulus fading, for increasing compliance during routine medical exams exhibited by 4 individuals with ASD. An indirect assessment identified problematic medical procedures, and a functional analysis showed that participants' disruptive behavior was maintained by escape from medical tasks. Differential reinforcement without extinction was insufficient in increasing medical compliance with 3 of 4 participants. The addition of a modified stimulus fading procedure that involved gradually introducing smaller components of problematic exam steps was effective in increasing medical compliance with all exam steps.